Kesytetty mammutti - Lukin, Karina (Suomen Geologinen Seura, 2021)
The article discusses the role of the mammoth in Siberian indigenous oral traditions focusing on Nenets mythology and shamanism. While the mammoth remains are typically attached to water-related gigantic beings in Siberian indigenous traditions, Nenets imagine the bones and tusks in terms of reindeer. On the one hand, there are narratives that tell about sihirtya, otherworldly beings living underground and having mammoth as their herd. On the other, Nenets shamans call mammoths to act as their helping spirits, when they want to visit the Underworld. In both images, the mammoth remains are interpreted in terms of reindeer, i.e., as a herd with which either sihirtya or the Nenets share space and interact. Additionally, the mythic images affect these views so that the mammoths are imagined as otherworldly living beings that can cross the borders of this and the other world and have an impact on our lives.